Prototype Pengembangan Sistem Informasi E-Commerce Berbasis Website - Dido Muhammad Hapsah; Isa Faqihuddin Hanif (Journal of Information System Research (JOSH), 2025)
This study develops a website-based e-commerce information system for the Ruang Style store. Several challenges faced by the store include limited marketing efforts and the lack of an online sales platform, which can lead to a decline in customers. The process of purchasing goods is still done manually, where customers must visit the store in person to buy products. Additionally, the sales and inventory data management is still done manually in the form of written records without an integrated database. The revenue from all sold items is also calculated manually, which increases the potential for errors in the calculation process. The goal of this research is to design a website-based e-commerce information system to help the store owner manage inventory and sales data, as well as facilitate customers in making transactions online so that they no longer need to visit the store physically. The research was conducted at Ruang Style store from April 2024 to December 2024. The prototype methodology was used, as the mockups were designed based on user evaluations. The study utilized PHP, MySQL, HTML, JavaScript, and CSS programming languages. The result of this research is the design of a website-based e-commerce information system. The conclusion of this study is that the design of the website-based store management information system can be successfully implemented on desktop browsers, and it successfully simplifies the marketing process for the store and facilitates customers in making transactions.